2011
DOI: 10.1016/j.ultrasmedbio.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Texture Analysis for Identifying Optimum Microbubble Concentration in 2-D Ultrasonic Particle Image Velocimetry

Abstract: Many recent studies on ultrasonic particle image velocimetry (Echo PIV) showed that the accuracy of two-dimensional (2-D) flow velocity measured depends largely on the concentration of ultrasound contrast agents (UCAs) during imaging. This article presents a texture-based method for identifying the optimum microbubble concentration for Echo PIV measurements in real-time. The texture features, standard deviation of gray level, and contrast, energy and homogeneity of gray level co-occurrence matrix were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The performance of the ultrasound imaging system used in this study is validated by applying it to a Newtonian fluid (PBS solution). Given that ultrasound agents have been commonly used for quantitative visualization of opaque flows 31 32 33 , microbubbles are used as tracer particles to measure velocity field of a PBS flow. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the ultrasound imaging system used in this study is validated by applying it to a Newtonian fluid (PBS solution). Given that ultrasound agents have been commonly used for quantitative visualization of opaque flows 31 32 33 , microbubbles are used as tracer particles to measure velocity field of a PBS flow. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies and the other existing works have identified texture analysis as being useful in the analysis of ultrasound images [11][13]. To date, plaque texture analysis has been applied to conventional 2D brightness mode (B-mode) ultrasound images and has been shown to have considerable success in identifying symptomatic carotid plaques including risk stratification and predicting stroke plaques.…”
Section: Introductionmentioning
confidence: 99%
“…The working fluid was pure water with a nominal viscosity of 0.0087 Pa S under 26 °C. Ultrasound contrast microbubbles, which had a concentration of (5.0–8.0) × 10 8 bubbles/ml as previously described in Niu et al [ 39 ], were seeded into the working fluid as the imaging particles. The fluid ultrasonic image was obtained by vevo2100 with a MS250 transducer (40 MHz), which offered a frame rate of 150 fps, focal depth of 5 mm and field of view (FOV) of 7 mm (depth) by 15 mm (width), to allow for a full view of plaque.…”
Section: Methodsmentioning
confidence: 99%